Representational layering in Functional Discource Grammar - Smit, Nels; Van Staden, Miriam (ALFA: Revista de Linguística, 2009)
The paper addresses the internal structure of layers at the Representational level in Functional Discourse Grammar (FDG), and proposes three adaptations of the representation of frames with respect to what is now standing practice (HENGEVELD; MACKENZIE, 2006; Forthcoming). Our main concern is a reappraisal of Dik’s (1989, 1997) original argumentation for the endocentric use of argument variables within restrictors of terms, which we argue are fundamental to FDG theory and should be generalised over all representational layers. Based on this view, we propose a transparent usage of square brackets, which embrace equipollent configurations of which the argument variable is part. This in turn reveals problems in the representation of the nuclear event description – the verb and its arguments – as an identifiable entity, which is an old problem in FG, as well as in the representation of reference modification. As a unified solution, we invoke exocentric layers to account for the special structural properties of these units. The result is a more consistent and transparent structure of representational frames in FDG.